IT project portfolio governance practice: An investigation into work design problems. Issue 2 (3rd April 2017) - Hansen, Lars Kristian; Kræmmergaard, Pernille; Mathiassen, Lars
ABSTRACT: As organizations increasingly invest in IT-enabled innovation, practitioners become dependent on IT project portfolio management to mitigate risks generated from multiple projects. However, our knowledge about IT project portfolio governance practices and how interactions between different structural arrangements enable or hinder effective portfolio management is limited. Against that backdrop, we report a case study of IT project portfolio governance in a Danish municipality. Drawing on work design theory (WDT), we identify three types of governance problems—hierarchical decomposition, modularity, and complex network problems—and we uncover the network of observed governance problems in the municipality's portfolio management practices. As a result, we offer two contributions: a detailed empirical account of IT project portfolio governance, and a demonstration of how WDT can help explain problems in IT project portfolio governance practices. In conclusion, we discuss how these results may inform future research and help organizations improve governance practices in similar contexts.